Perspektif Islam terhadap Penggunaan Cadaver dalam Proses Pembelajaran Ilmu Kedokteran - Zahratu Al Bilqis Jasmine Anwar; Naila Dinda Qurratul'ain; Safira Rizkiya Putri Syaiful (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to analyze the Islamic perspective on the use of cadavers in the medical education process, focusing on the views of Muslim medical students. The research method employed is a qualitative approach, with data collection through in-depth interviews and focus groups involving medical students from several universities. The analysis results indicate that students face ethical challenges regarding the use of cadavers, yet they also recognize the importance of this experience for developing necessary medical skills. The majority of respondents expressed that although there are moral dilemmas, the use of cadavers is seen as an important tool for understanding anatomy and enhancing competence in medical practice. This study concludes that dialogue between religious values and professional needs in medical education is essential to create a better understanding of cadaver use among Muslim medical students.